2018
DOI: 10.1002/maco.201810312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graphene on the electrochemical protection of zinc‐rich coatings

Abstract: The effect of graphene on electrochemical protection of zinc‐rich coatings was studied by electrochemical impedance spectroscopy (EIS) and the monitoring of open circuit potential (OCP) versus time of immersion. The obtained results show that addition of 2.5 wt% graphene to zinc‐rich coating prolongs the lifetime of cathodic protection to mild steel immersion in sodium chloride solution. On the basis of these consistent finds, two protective mechanisms of graphene are assumed. On the one hand, the embedded gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…This phenomenon indicated that Fe 2 O 3 /NGr particles inhibited the cathodic reduction reaction in the system, which suggests that the cathodic reduction reaction is directly proportional to the addition of conducting particles and the percolation path. , The highly conductive NGr filled the voids between the spherical Zn particles, as confirmed by FE-SEM images. It interconnected the particles, enhanced the conductivity, and reached the galvanic action required to provide cathodic protection. , The GC-5 showed more galvanic action than GC-3 and GC-4 because of the higher amount of NGr (1.5%).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…This phenomenon indicated that Fe 2 O 3 /NGr particles inhibited the cathodic reduction reaction in the system, which suggests that the cathodic reduction reaction is directly proportional to the addition of conducting particles and the percolation path. , The highly conductive NGr filled the voids between the spherical Zn particles, as confirmed by FE-SEM images. It interconnected the particles, enhanced the conductivity, and reached the galvanic action required to provide cathodic protection. , The GC-5 showed more galvanic action than GC-3 and GC-4 because of the higher amount of NGr (1.5%).…”
Section: Resultsmentioning
confidence: 97%
“…It interconnected the particles, enhanced the conductivity, and reached the galvanic action required to provide cathodic protection. 28,44 The GC-5 showed more galvanic action than GC-3 and GC-4 because of the higher amount of NGr (1.5%).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Graphene, a phenomenal nanomaterial, has drawn huge attention over the past decade, owing to its strictly two‐dimensional structure, giant carrier mobility, high thermal conductivity, and brilliant mechanical properties . To date, the use of graphene as a corrosion protection barrier has been widely reported, based on its shielding effect (impermeability to oxygen, water, and chloride ions) and excellent electrical conductivity. However, graphene sheets can easily aggregate together owing to their high specific surface area and strong van der Waals forces, which limits their applications in polymer composites .…”
Section: Introductionmentioning
confidence: 99%